Reactivation of human brain homogenate cholinesterases inhibited by Tabun using newly developed oximes K117 and K127 - Kuca, Kamil; Cabal, Jiri; Jung, Yung Sik; Musilek, Kamil; Soukup, Ondrej; Jun, Daniel; Pohanka, Miroslav; Musilova, Lucie; Karasová, Jana; Novotný, Ladislav; Hrabinova, Martina (Basic & clinical pharmacology & toxicology, 2009)
Newly developed acetylcholinesterase reactivators K117 [1,5-bis(4-hydroxyiminomethylpyridinium)-3-oxapentane dichloride] and K127 [(1-(4-hydroxyiminomethylpyridinium)-5-(4-carbamoylpyridinium)-3-oxapentane dibromide)] were tested for their potency to reactivate tabun-inhibited human brain cholinesterases. Pralidoxime and trimedoxime were chosen as standard reference reactivators. Human tissue was used, as that was closer on the real treatment of human beings. As a result, oxime K127 was found as the best tested reactivator according to the constant k(r), characterizing the overall reactivation process. On the contrary, the maximal reactivation ability expressed as percentage of reactivation was the best for trimedoxime. This differences were caused as a result of using the enzyme from different species. Due to this, experiments on human tissue should be conducted after in vitro and in vivo tests on animals to eliminate such important failures of promising oximes.
Keywords: Pyridinium Compounds; organofosfáty; Cholinesterase Reactivators; pyridinové sloučeniny; lidé; senioři; mužské pohlaví; Oximes; cholinesterasové inhibitory; Cholinesterase Inhibitors; Male; Aged; Brain; Organophosphates; reaktivátory cholinesterasy; mozek; oximy; Humans